Learning intensity effects in students' mental and physical health – Evidence from a large scale natural experiment in Germany. (December 2018) - Hofmann, Sarah; Mühlenweg, Andrea
Abstract: In this study, we analyze the health effects of a recent education reform in Germany exposing students to increased learning intensity. The reform shortened the higher secondary education track by one year. As the overall curriculum required for graduation was held constant, this led to an increase in instruction hours in the remaining school years. The reform was introduced at different points in time across federal states, providing us with a difference-in-difference setup for analysis. Based on data from the German Socio-Economic Panel Study (SOEP), our results imply that the reform significantly reduced adolescents' self-rated mental health status. The overall effect on the Mental Component Summary Score (MCS) is about a quarter of a standard deviation. Examining MCS sub-dimensions, we find detrimental effects of the reform on vitality and on emotional balance. We do not observe a significant reform effect on the aggregated physical health measure.